Combination Therapy of Albumin-Bound Paclitaxel and Carboplatin as First Line Therapy in a Patient with Ovarian Cancer - K. N Srinivasan; Amit Rauthan; R. Gopal (Case Reports in Oncological Medicine, 2014)
Background. Ovarian cancer is the ninth most common cancer among women and causes more deaths than any other type of female reproductive cancer. Albumin-bound paclitaxel is known to increase intratumoral concentration of the paclitaxel by a receptor-mediated transport process across the endothelial cell wall, thereby breaching the blood/tumor interface. We present below three cases in which nab-paclitaxel based chemotherapy has been used in different settings for patients with ovarian cancer. Case Presentation. In the first case nab-paclitaxel was used along with carboplatin in adjuvant setting, in the second case, nab-paclitaxel was used along with carboplatin and bevacizumab as second line chemotherapy in a relapsed ovarian cancer case, and the third case delineates the use of nab-paclitaxel along with cisplatin as third line chemotherapy. Conclusion. In all the three scenarios, patients tolerated the chemotherapy well, as well as responding well to nab-paclitaxel based chemotherapy. The patients are currently on long-term follow-up and have been having an uneventful postchemotherapy.